The effects of short bouts of ergometric exercise for severely burned children in intensive care: A randomized controlled trial. (August 2022) - Chao, Tony; Parry, Ingrid; Palackic, Alen; Sen, Soman; Spratt, Heidi; Mlcak, Ronald P.; Lee, Jong O.; Herndon, David N.; Wolf, Steven E.; Branski, Ludwik K.; Suman, Oscar E.
Objective: To determine the effects of short bouts of ergometric exercises on the number of days in the burn intensive care unit (ICU), body mass, and functional ambulation. Design: Multi-center, randomized controlled trial. Setting: Burn intensive care unit. Participants: Children ages 7–17 with severe burns covering over 30% total body surface area (TBSA). Intervention: All patients received standard of care (Control) with the experimental group receiving additional exercise with a cycle ergometer (Exercise). Main measures: The number of days in the ICU, total weight, lean body mass (LBM), and functional ambulation were taken shortly after randomization and again within one week of the scheduled hospital discharge. Results of outcomes are expressed as median ± interquartile range (IQR), unless otherwise noted (e.g. demographics). Results: Fifty-four severely burned children (n = 18 Control, n = 36 Exercise) were included. The average ± standard deviation for age was 12 ± 3 years and TBSA was 48 ± 16%. The median ± IQR ICU days for Control was 46 ± 51 days vs 31 ± 29 days for Exercise. The median total weight loss for Control was 2.2 ± 1.2 kg vs 1.8 ± 1.4 kg in Exercise. Control lost 0.75 ± 0.8 kg of LBM vs 0.46 ± 0.43 kg in Exercise. Both groups showed significant improvement in functional ambulation ( p < 0.01). However, exercise did not add additional benefits. Conclusion: Short bouts of ergometric exercises are feasible for severely burned patients while receiving care in the ICU but did not add additional benefits.